Iowa Birdline update, December 7, 1992 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1992)
Email of Iowa Birdline updates for December 7, 1992. The highlights for the update include sightings of a male Evening Grosbeak, ten Snow Buntings, and a Northern Goshawk. Also included are handwritten notes with sightings of a lingering American White Pelican at Whitebreast Park in Marion County. Epson - sheet feed/flatbed